Pengaruh Perkembangan Bandara Internasional Adi Soemarmo terhadap Perubahan Guna Lahan Perdagangan dan Jasa pada Koridor Jalan Adi Sucipto di Kota Surakarta-Kabupaten Karanganyar - Fitri Nur Cahyani; Winny Astuti; Galing Yudana (ARSITEKTURA, 2017)
Adi Soemarmo International Airport is one of the terminal air transportation, which is currently being carried out development. Empirically, Adi Soemarmo International Airport have a direction towards the development of Surakarta is a corridor that connects the Adi Soemarmo International Airport with the city center of Surakarta. One of the corridors that developed along the development of Adi Soemarmo International Airport is an Adi Sucipto road corridor. Development in Adi Sucipto road corridor are emerging land use of commercial activities. The problem in this research is how to influence the development of Adi Soemarmo International Airport to changes in land use of trade and services in the Adi Sucipto road corridor? The purpose of research is influence the development of Adi Soemarmo International Airport to changes in land use of trade and services in the corridor of Adi Sucipto road corridor. The method used is the deductive research methods with quantitative research. The analysis technique used is descriptive analysis. Conclusions from this research is the development of Adi Soemarmo International Airport influence to changes in land use of trade and services in the corridor of Adi Sucipto road corridor. The degree of influence can be divided into three classifications that is high levels of influence, medium levels of influence, and low levels of influence. High levels of influence, that is (1) the influence of the facility of Adi Soemarmo International Airport to function of land use and floor space ratio of trade and service in the corridor of Adi Sucipto road. (2) the influence of of the accessibility of Adi Soemarmo International Airport to function of land use and floor space ratio of trade and service in the corridor of Adi Sucipto road. Keywords: airport, road corridor, land use